The role of plants in traditional medicine and current therapy: A case study from North part of Kashmir Himalaya - Khoja, Aadil Abdullah; Waheed, Muhammad; Haq, Shiekh Marifatul; Bussmann, Rainer W. (Ethnobotany Research and Applications, 2024)
Background: In many rural areas, especially in developing nations, medicinal plants serve as the main source of the healthcare systems. The purpose of this study was to document the therapeutic plants used by the local population in the Kashmir Himalayas. Methods: Ethnobotanical data were collected through semi-structured questionnaire was used to conduct one-on-one interviews and group discussions with selected informants. Use value (UV), relative frequency of citation (RFC), and informant consensus factor (ICF) were three quantitative indicators used to assess the homogeneity of the ethnobotanical data. Results: A total of 72 medicinal plants belonging to 41 different families were reported. Asteraceae, Lamiaceae and Polygonaceae were the dominant families. Leaves were the most commonly plant part used and infusion the dominant plant preparation. Gastrointestinal and hepatobiliary conditions, followed by dermatological disorders and musculoskeletal conditions were treated by highest number of plant species. Highest UV was reported for Artemisia absinthium (0.65), Rheum webbianum (0.59) and highest RFC is reported for Arnebia benthamii (0.61), Taraxacum officinale (0.59). The highest IFC values are reported for Gynecological disorders (0.99), Muscular and joint diseases (0.98) disease categories. Out of 72 medicinal plants reported 59 medicinal plants were used for different ethno-biological uses other than medicinal values. A total of 8 medicinal plants were exotic species, and 14 were reported in IUCN red list. Conclusion: Due to increasing human activity and environmental degradation, traditional knowledge on plant use is slowly disappearing in many regions. The promotion of the transmission of traditional knowledge requires immediate action. In order to boost local economic development and uphold the principle of biodiversity protection, it is also necessary to ensure the sustainable use of medicinal plants. Keywords; Kashmir, local communities, Medicinal plants, Traditional therapies.